Application of Auditory, Intellectually, Repetition Model Assisted by Kahoot to Improve Understanding of Temperature and Expansion Concepts in Class XI - Risnauli, Amelia; Fauza, Mitri Irianti, Naila; Irianti, Mitri (Kasuari: Physics Education Journal (KPEJ), 2025)
In improving students' conceptual understanding of a learning material, an efficient and effective learning model is needed. One of the efficient and effective learning models in improving conceptual understanding is the Auditory, Intellectually, Repetition learning model assisted by Kahoot. This study aims to describe students' conceptual understanding by implementing the Auditory, Intellectually, Repetition learning model assisted by Kahoot on the material of temperature and expansion. In addition, this study was conducted to determine the differences in students' conceptual understanding using the Auditory, Intellectually, Repetition learning model assisted by Kahoot with conventional learning models on the material of temperature and expansion as a solution to improve the conceptual understanding of grade XI students on the material of temperature and expansion. This study used a quasi-experimental research type with a posttest-only control group design. The research data were in the form of posttest results of conceptual understanding which were processed quantitatively. The results showed that the experimental class had a higher average conceptual understanding ability score than the control group. The experimental class obtained an average score of 85.03 with a very good category and the control class obtained an average of 75.69 with a good category.